Remaja Akhir dan Kecenderungan Risk Taking Behavior: Peran Kontrol Diri dan Konformitas - Pujia Tri Agustin; Puspa Rahayu Utami Rahman; Yulyanti Minarsih (EduInovasi: Journal of Basic Educational Studies, 2025)
Adolescents are a vulnerable age group prone to engaging in various risk-taking behaviors as part of their identity exploration and exposure to social influences. This study aimed to examine the effect of self-control and conformity on the tendency of risk-taking behavior among late adolescents in Karawang. The research employed a quantitative approach with a causal design. The sample consisted of 388 adolescents aged 18–22 years, selected through convenience sampling. The instruments used included the Risk Taking Behavior Scale, the Brief Self-Control Scale (BSCS), and the Conformity Scale. Data were analyzed using multiple linear regression with SPSS. The results indicated that self-control significantly affects the tendency of risk-taking behavior. In addition, conformity also influences the tendency of risk-taking behavior. Simultaneously, self-control and conformity were proven to have an effect on the tendency of risk-taking behavior, contributing 77.8%.